A Design of Body Mass Index (BMI) and Body Fat Percentage Device Using Fuzzy Logic - Irmalia Suryani Faradisa; Radimas Putra Muhammad; Dyah Ayu Girindraswari (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2022)
Nutritional status is something that should consider because it is related to the level of health. Poor health can lead to malnutrition and death. The purpose of this study is to create a tool with a system that can determine the value and category of Body Mass Index (BMI) automatically using fuzzy logic to maintain nutritional status. However, because BMI can only decide underweight or overweight, it is necessary to determine the fat percentage based on the British Journal of Nutrition. In determining BMI and fat percentage, a load cell weight sensor with a capacity of 200 kg as a bodyweight measurement, an ultrasonic sensor HCSR-04 as a body height measurement, and a keypad that functions to enter a name, age, gender, and type of activity data. Database in this system can provide and store easier and real-time data, so the data output is accessible directly. The results are analyzed by comparing the measurement with standard tools. The BMI test taken 5 times, showed that the categories in the system (very thin, thin, normal, heavy, obese) were the same as the MATLAB test and manual calculations. Meanwhile, the results of testing body fat percentage taken 4 times also show the same category as the Body Monitor tool. So, this system can use for daily to monitor the condition of nutritional status and fat percentage in real-time.